PVDF powder
Patent Information
- Application Number
- JP2023565858
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-29
- Filing Date
- 2022-04-28
- Publication Date
- 2025-04-07
AI Technical Summary
Existing vinylidene fluoride (VDF) polymers produced by suspension and emulsion polymerization face issues with particle size and porosity, leading to viscosity increases and settling problems in dispersions, with mechanical grinding resulting in irregular shapes.
A VDF polymer powder with a median particle size of 15-50 microns and a total pore volume of 0.70-2.00 mL/g is produced through suspension polymerization, using partially hydrolyzed polyvinyl alcohol as a suspending agent and controlled stirring conditions, resulting in rounded primary particles.
The method achieves stable VDF polymer slurry mixtures with high solids content, preventing sedimentation and enabling easy suspension in water, suitable for applications in batteries, electrodes, and composite materials.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to European Patent Application No. 21305550.2, filed April 29, 2021, the entire contents of which are incorporated herein by reference for all purposes.
[0002] The present invention relates to vinylidene fluoride polymer powders comprising rounded particulates, methods for making said vinylidene fluoride polymer powders, and articles prepared from the vinylidene fluoride polymer powders. [Background technology]
[0003] Vinylidene fluoride polymers (hereinafter "VDF polymers") are used in several applications where the durability, chemical inertness, and other advantageous properties of VDF polymers are highly beneficial. VDF polymers find utility in architectural coatings, membrane manufacturing, chemical industrial coatings, and / or oil and gas (O&G) applications.
[0004] VDF polymers are also widely used as binders for the manufacture of electrodes, especially cathodes, for the preparation of composite separators and / or for coating porous separators for use in non-aqueous electrochemical devices such as batteries, preferably secondary batteries, and electric double layer capacitors.
[0005] VDF polymers are also used in the preparation of fibre-reinforced polymer composites, i.e. those which use continuous fibres, e.g. carbon or glass fibres, as the main structural component and a thermosetting or thermoplastic polymer as the matrix component.
[0006] Some of the applications mentioned above rely on the use of solvent or water based systems to convert the VDF polymer into the final article.
[0007] VDF polymers can be obtained by polymerization of vinylidene fluoride monomers (difluoro 1,1-ethylene or VDF) either by suspension or emulsion polymerization.
[0008] Post-processing of emulsion polymerized VDF polymer usually produces fine powders with higher surface area and porosity than suspension polymerized VDF polymer.
[0009] On the other hand, the high porosity of emulsion polymerized VDF polymer often leads to particle swelling in solvents or liquids that have some affinity for PVDF, resulting in high viscosity VDF polymer dispersions. As a result, the amount of VDF polymer particles that can be dispersed is limited by the viscosity of the system.
[0010] Suspension polymerized VDF polymers are characterized by a denser particle structure than emulsion polymerized VDF polymers. They are usually characterized by a larger average size, which increases the tendency of the particles to settle when incorporated into a dispersion. Although it is known to reduce the particle size by mechanical grinding, the resulting particles are characterized by an irregular shape.
[0011] Surprisingly, it has been found that VDF polymer powders comprising primary particles with a median particle size d50 between 15 and 50 microns and a total pore volume between 1.00 and 2.00 mL / g can be used to prepare VDF polymer slurry mixtures with a good balance between high solids content and high stability with respect to settling of the solids. The primary particles are further characterized by a rounded shape as defined hereinafter. The VDF polymer powders are obtained by suspension polymerization. Summary of the Invention
[0012] In a first aspect, the present invention relates to a VDF polymer powder comprising primary particles having a median particle size d50 in the range of 15-50 microns, measured by laser diffraction according to ISO 13320, and a total pore volume Vpt of 0.70-2.00 mL / g, measured by mercury porosimetry. In one embodiment of the present invention, the particles have a rounded shape. Preferably, the primary particles have a circularity ratio RR of 0.70-1.00. In a further embodiment, the VDF polymer powder has been obtained by suspension polymerization.
[0013] A second aspect of the invention is a method for producing a VDF polymer powder, comprising the step of polymerizing VDF in the presence of a polyvinyl alcohol suspending agent with vigorous stirring.
[0014] A further aspect of the invention is a slurry comprising water and a VDF polymer powder according to the first aspect of the invention. [Brief description of the drawings]
[0015] [Figure 1] 1 is a scanning electron microscope image of the VDF polymer powder of Example 7. [Diagram 2] 1 is a scanning electron microscope image of VDF polymer A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] definition In contrast to the use of "consisting of," the use of "including, containing, comprising," or "having" and variations thereof is intended to encompass the items listed thereafter and additional items. The use of "a" or "an" is intended to encompass "one or more." All numerical ranges described herein describing physical properties or concentrations are intended to include every value from the lower value to the upper value of the range, including the endpoints. For example, a concentration range of 1% to 50% is intended to be abbreviated and explicitly disclose values between 1% and 50%.
[0017] For the purposes of the present invention, "primary particle" is intended to refer to the smallest separate identifiable entity observable by laser diffraction techniques performed in accordance with ISO 13320.
[0018] It is intended that primary particles can be distinguished from agglomerates, which are clusters of primary particles held together by weak physical interactions, obtained at the end of the polymerization of the VDF monomer, which are separated from the reactor liquid, washed and then dried.
[0019] The term "span" is used herein to refer to the width of the primary particle size distribution, defined as the ratio (d90-d10) / d50, d50 is the median particle size, below (and above) which 50% of the total volume of particles is found, d10 represents the particle size below which 10% of the total volume of particles is found, · d90 represents the particle size below which 90% of the total volume of the particles is found.
[0020] For the avoidance of doubt, in this specification the values d10, d50 and d90 refer to the diameter of the primary particles of the VDF polymer.
[0021] A first object of the present invention is therefore a VDF polymer powder comprising primary particles having a median particle size d50 in the range of 15 to 50 microns, measured by laser diffraction according to ISO 13320, and a total pore volume Vpt of 0.70 to 2.00 mL / g, measured by mercury porosimetry.
[0022] As used herein, the term "VDF polymer" refers to a polymer that contains more than 80 mol %, preferably more than 85 mol %, or even more than 90 mol % of repeat units derived from the polymerization of vinylidene fluoride monomers (difluoro 1,1-ethylene, VF2 or VDF).
[0023] The VDF polymer may be a homopolymer, i.e. a polymer containing only repeat units derived from VDF.
[0024] Alternatively, the VDF polymer may contain, in addition to VDF monomers, repeat units different from VDF which are derived from the polymerization of ethylenically unsaturated monomers different from VDF.
[0025] Said ethylenically unsaturated monomer different from VDF may be selected from the group consisting of fluorinated or non-fluorinated monomers.
[0026] Fluorinated monomers are ethylenically unsaturated monomers that contain at least one fluorine atom.
[0027] Non-limiting examples of fluorinated monomers different from VDF include in particular: (i) C2-C8 fluoroolefins, such as trifluoroethylene (TrFE), tetrafluoroethylene (TFE) and hexafluoropropylene (HFP); (ii) perfluoroalkylethylene of the formula CH2=CH-Rf0 (wherein Rf0 is a C2-C6 perfluoroalkyl group); (iii) Chloro- and / or bromo- and / or iodo-C2-C6 fluoroolefins, such as chlorotrifluoroethylene (CTFE); (iv) perfluoroalkyl vinyl ethers of the formula CF2=CFORf1 (wherein Rf1 is a C1-C6 perfluoroalkyl group), such as perfluoromethyl vinyl ether (PMVE) and perfluoropropyl vinyl ether (PPVE); (v) (per)fluorooxyalkyl vinyl ethers of the formula CF2=CFOX0, where X0 is a C1-C12 oxyalkyl group or a C1-C12 (per)fluorooxyalkyl group having one or more ether groups, such as a perfluoro-2-propoxy-propyl group; (vi) (per)fluoroalkyl vinyl ethers of the formula CF2=CFOCF2ORf2, where Rf2 is a C1-C6 (per)fluoroalkyl group, such as -CF3, -C2F5, -C3F7, or a C1-C6 (per)fluorooxyalkyl group having one or more ether groups, such as -C2F5-O-CF3; (vii) functional (per)fluorooxyalkyl vinyl ethers of formula CF2=CFOY0, where Y0 is selected from C1-C12 alkyl or (per)fluoroalkyl groups, C1-C12 oxyalkyl groups and C1-C12 (per)fluorooxyalkyl groups having one or more ether groups, and Y0 contains a carboxylic or sulfonic acid group in its acid, acid halide or salt form; (viii) Fluorodioxoles, in particular perfluorodioxoles; (ix) vinyl fluoride, and mixtures thereof.
[0028] The most preferred fluorinated comonomers are chlorotrifluoroethylene (CTFE), trifluoroethylene (TrFE), tetrafluoroethylene (TFE), hexafluoropropylene (HFP), perfluoromethylvinylether (PMVE).
[0029] The VDF polymer may contain from 0.1 to 15.0 mol % of fluorinated monomers different from VDF, relative to the total number of moles of the polymer.
[0030] Preferably, the VDF polymer is semi-crystalline and contains 0.1 to 10.0 mol %, preferably 0.3 to 5.0 mol %, more preferably 0.5 to 3.0 mol % of repeat units derived from a fluorinated monomer other than VDF.
[0031] It is understood that chain ends, defects, or other impurity type sites may be included in the VDF polymer without impairing the properties of the polymer.
[0032] Instead of or in addition to repeat units derived from fluorinated monomers different from VDF, the VDF polymer may also contain repeat units derived from ethylenically unsaturated monomers that do not contain fluorine atoms. Examples of non-fluorinated monomers are in particular hydrophilic monomers of formula (I) (hereinafter "hydrophilic monomers"): [ka] (In the formula, R1, R2 and R3 are equal to or different from each other and are independently selected from a hydrogen atom and a C1-C3 hydrocarbon group; - R X is a C1-C aryl group containing at least one functional group selected from hydroxyl, carboxyl, epoxide, ester and ether groups; 20 (the hydrocarbon moiety).
[0033] In one embodiment, the hydrophilic monomer is a monomer of formula (I) as defined above, where Rx is a C1-C5 hydrocarbon moiety containing at least one carboxyl group.
[0034] In another embodiment, the hydrophilic monomer is selected from compounds of formula (Ia): [ka] (In the formula, R1, R2 and R3 are equal to or different from each other and are independently selected from a hydrogen atom and a C1-C3 hydrocarbon group; - R H is hydrogen or a C1-C5 hydrocarbon moiety containing at least one carboxyl group).
[0035] Non-limiting examples of monomers of formula (Ia) include, inter alia, acrylic acid, (meth)acrylic acid, and mixtures thereof.
[0036] In a further embodiment, the hydrophilic monomer is selected from compounds of formula (Ib): [ka] (In the formula, R1, R2, and R3 are equal to or different from each other and independently represent a hydrogen atom or a C1-C3 hydrocarbon group; R OH is hydrogen or a C1-C5 hydrocarbon moiety containing at least one hydroxyl group.) Non-limiting examples of hydrophilic monomers of formula (Ib) are hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxyethylhexyl (meth)acrylate.
[0037] The hydrophilic monomer is advantageously selected from the group consisting of: - Hydroxyethyl acrylate (HEA) of the formula: [ka] - 2-Hydroxypropyl acrylate (HPA) of any of the following formulas: [ka] - and mixtures thereof.
[0038] The hydrophilic monomers are preferably randomly distributed in the VDF polymer.
[0039] The VDF polymer may contain at least 0.02 mol %, more preferably at least 0.20 mol %, of repeat units derived from hydrophilic monomers.
[0040] The VDF polymer preferably contains up to 5.0 mol %, more preferably up to 3.0 mol %, even more preferably up to 1.5 mol % of repeat units derived from hydrophilic monomers.
[0041] In one embodiment of the invention, the VDF polymer preferably comprises, and more preferably consists of, repeat units derived from: at least 80.00 mol %, preferably at least 85.00 mol %, more preferably at least 90.00 mol % vinylidene fluoride (VDF), 0.01 mol % to 3.00 mol %, preferably 0.05 mol % to 1.50 mol %, more preferably 0.15 mol % to 1.0 mol % of hydrophilic monomers of formula (I) as defined above, including those of formulae (Ia) and (Ib); Optionally, 0.50 mol % to 3.00 mol % of repeat units derived from a fluorinated monomer other than VDF.
[0042] The VDF polymer powder according to the invention comprises primary particles with a median particle size d50, measured by laser diffraction according to ISO 13320, of 15 to 50 microns.
[0043] The VDF polymer powder comprises primary particles with a median particle size d50 of more than 15 microns, preferably more than 20 microns and / or less than 50 microns, preferably less than 49 microns or even less than 45 microns. In an advantageous embodiment, the VDF powder typically comprises primary particles with a median particle size d50 of 20-50 microns, 20-49 microns, 22-40 microns or even 22-35 microns.
[0044] Advantageously, the VDF polymer powder has a span of the primary particle size distribution of less than 2.0, or even less than 1.5.
[0045] The VDF polymer powder comprises primary particles characterized by a total pore volume, measured by mercury porosimetry as described in detail below, of 0.70 to 2.00 mL / g. The total pore volume may be greater than 0.75 mL / g or even greater than 0.80 mL / g.
[0046] In one embodiment of the present invention, the primary particles of the VDF polymer have a rounded shape. Preferably, they have a circularity ratio RR between 0.70 and 1.00, preferably between 0.75 and 1.00.
[0047] The circularity ratio RR is defined as the ratio between the minimum and maximum Feret diameter, where the Feret diameter is defined as the distance between two parallel tangents on opposite sides of the particle's silhouette.
[0048] A circularity ratio close to 1.00 indicates very round particles, while a circularity ratio close to zero indicates non-round particles that resemble the shape of fibers.
[0049] The circularity ratio was determined by image analysis of pictures taken with a scanning electron microscope Jeol JSM-7610F with an accelerating voltage adjusted to 5 kV (picture size: 1280 × 1024 pixels). Image analysis was performed using Zen ZEISS software with the "Image Analysis" and "Intellesis" modules as described in the experimental section.
[0050] The VDF polymer powder according to the invention comprises at least 55%, preferably 65%, more preferably 75%, by number of primary particles having a circularity ratio of more than 0.80.
[0051] The VDF polymer powder was obtained by suspension polymerization.
[0052] A second object of the present invention is a method for producing the VDF polymer powder according to the first object of the present invention.
[0053] The process of the present invention is a polymerization carried out in aqueous suspension.
[0054] In one embodiment, the process for the preparation of a VDF polymer powder comprises a step of polymerizing VDF in aqueous suspension, and optionally one or more ethylenically unsaturated monomers copolymerizable therewith, in the presence of a water-soluble suspending agent selected from the group of partially hydrolyzed polyvinyl alcohol polymers, said polymerization being carried out at an agitation speed N (expressed in rpm) for a given reactor diameter D (expressed in meters) of: |D| 2 / 3 ×|N|≧250 in a reactor under stirring, In the formula, |D| represents the absolute value of the reactor diameter D expressed in meters, and |N| represents the absolute value of the stirring speed expressed in rpm.
[0055] In a preferred embodiment, the stirring speed N is |D| 2 / 3 ×|N|≧270 This is the speed at which
[0056] The upper limit of the stirring speed N is limited only by the system configuration, but the formula |D| defined above 2 / 3 ×|N| usually does not exceed 1000, usually does not exceed 800, and even usually does not exceed 700.
[0057] In one embodiment of the method, the formula |D| 2 / 3 It has been found to be advantageous for x|N| to be comprised between 250 and 600, or even between 270 and 500, and possibly between 270 and 400.
[0058] In another embodiment, the method for preparing a VDF polymer powder comprises the step of polymerizing VDF in aqueous suspension, optionally with one or more ethylenically unsaturated monomers copolymerizable therewith, in the presence of a water-soluble suspending agent selected from the group of partially hydrolyzed polyvinyl alcohol polymers, said polymerization being carried out according to a Reynolds number Re=ρ.Nd I 2 / μ (where ρ is the density of water (kg / m 3 ), N is the impeller revolutions per second (1 / s), and d I The reaction is carried out in a reactor under stirring characterized by an agitation speed such that the viscosity of the water at the reaction temperature (Pa·s) is greater than 24000, preferably greater than 25000, more preferably greater than 27000, and even more preferably greater than 30000. The maximum Reynolds number is not particularly limited, but is usually preferably less than 100000, more preferably less than 90000, and even more preferably less than 50000.
[0059] For the purposes of the present invention, polymerization in aqueous suspension refers to a process in which the reaction medium is formed by an organic phase to which water is added. Water is typically added to facilitate the dispersion of heat that occurs during the reaction. The organic phase can be formed by the monomers themselves without the addition of a solvent, or by dissolving the monomers in a suitable organic solvent in the presence of a suitable organic initiator and a water-soluble suspending agent.
[0060] A water-soluble suspending agent suitable for the method of the present invention is a partially hydrolyzed polyvinyl alcohol polymer. The expression "partially hydrolyzed polyvinyl alcohol polymer" is used herein to refer to a polymer obtained by partial hydrolysis of a poly(vinyl acetate) polymer. A poly(vinyl acetate) polymer is defined as a polymer composed of repeating units derived from vinyl acetate.
[0061] Partially hydrolyzed poly(vinyl alcohol) polymers are typically compositions that include partially hydrolyzed poly(vinyl acetate) and poly(vinyl alcohol).
[0062] Partially hydrolyzed poly(vinyl alcohol) polymers are commercially available and are available over a range of molecular weights and degrees of hydrolysis.
[0063] The degree of hydrolysis of the partially hydrolyzed poly(vinyl alcohol) polymers used in the process of the present invention is usually at least 50%, preferably at least 55%.
[0064] The amount of at least one partially hydrolyzed poly(vinyl alcohol) polymer used in the polymerization is typically from 0.1 to 2.0 g / kg total monomers, preferably from 0.5 to 1.5 g / kg total monomers.
[0065] The polymerization reaction can be carried out under conditions of temperature and pressure such that the more abundant monomer, i.e. VDF, is present in a sub- or supercritical state.
[0066] More preferably, the polymerization is carried out at an initial water / monomer (g / g) ratio (hereinafter "Rwm") greater than 3.00, preferably greater than 5.00.
[0067] Typically, the process of the invention is carried out at a temperature of at least 10°C, preferably at least 25°C, more preferably at least 45°C.
[0068] The pressure is typically maintained at a value greater than 2.5 MPa, preferably greater than 5.0 MPa, even more preferably greater than 7.5 MPa.
[0069] The process of the present invention is carried out in the presence of a radical initiator. While the choice of radical initiator is not particularly limited, it is understood that initiators suitable for the process according to the present invention are selected from compounds capable of initiating and / or accelerating the polymerization process.
[0070] Among the radical initiators that can be advantageously used in the method of the present invention, mention can be made of organic radical initiators.Non-limiting examples of suitable organic radical initiators include acetylcyclohexanesulfonyl peroxide; diacetylperoxydicarbonate; dialkylperoxydicarbonates, such as diethylperoxydicarbonate, dicyclohexylperoxydicarbonate, di-2-ethylhexylperoxydicarbonate; tert-butylperneodecanoate; 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile; tert-butylperpivalate; tert-amylperpivalate; dioctanoylperoxide; dilauroylperoxide; 2,2'-azobis(2,4dimethylvaleronitrile); tert-butylazo-2-cyanobutadiene; Examples of peroxides that may be used include, but are not limited to, tert-butyl peroxyisopropyl carbonate, tert-butyl peracetate, 2,2'-bis(tert-butylperoxy)butane, dicumyl peroxide, di-tert-amyl peroxide, di-tert-butyl peroxide (DTBP), p-methane hydroperoxide, pinane hydroperoxide, cumene hydroperoxide, and tert-butyl hydroperoxide.
[0071] The process of the present invention typically further comprises separating the VDF polymer obtained at the end of the polymerization step from the aqueous medium, which is typically carried out by filtration.
[0072] The VDF polymer obtained by the process of the present invention is typically dried at a temperature typically comprised between 30°C and 120°C, preferably between 50°C and 90°C.
[0073] The Applicant has surprisingly found that the process according to the invention makes it possible to obtain VDF polymer in the form of primary particles having a median particle size d50 between 15 and 50 microns and a total pore volume Vpt between 0.70 and 2.00 mL / g.
[0074] In the prior art methods, the grinding process of typically large VDF polymer particles could obtain particles with a size distribution with a d50 value of less than 50 microns and a pore volume in the range of 0.70-2.00 mL / g. However, this method is very time-consuming and very energy-intensive. In addition, the particles obtained by grinding are not round.
[0075] A further object of the present invention is a composition comprising water and the primary particles of VDF polymer which are the first object of the present invention. The VDF polymer primary particles of the present invention are easily suspended in water by using any suitable non-ionic surfactant and hardly decant over time. Surprisingly, it has been found that, regardless of the general density nature of the primary particles, it is possible to obtain an aqueous composition which is stable over time, i.e. does not cause sedimentation of the particles, when the particles have a d50 in the range of 15 to 50 microns.
[0076] The composition may further comprise a surfactant, typically a non-ionic surfactant. Other additives may be used as dispersion densifiers or stabilizers.
[0077] Preferably, the composition comprises from 20% to 60% by weight, more preferably from 45% to 55% by weight, of primary particles according to the invention relative to the total weight of the composition.
[0078] The VDF polymer powder of the present invention, and liquid compositions comprising said VDF polymer powder, can be used for the manufacture of many articles.
[0079] In one embodiment, the powders and compositions can be used in the manufacture of binders and electrodes for primary and secondary batteries.
[0080] The VDF polymer powders according to the invention are also particularly suitable for the preparation of films and membranes, among which mention may be made of porous membranes, in particular for water filtration.
[0081] The VDF polymer powder of the present invention can also be advantageously used for the preparation of fiber-reinforced composite materials.
[0082] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements of this application to the extent that a term may be unclear, this statement shall control.
[0083] The invention will now be described in more detail with reference to the following examples, the purpose of which is merely illustrative and not limiting the scope of the invention.
[0084] Analysis method The properties of the VDF polymer powders of the present invention were determined using the methods described hereinafter.
[0085] Pore volume determination by mercury porosimetry. Pore volume and pore size distribution were determined using a Micromeritics AutoPore® IV9520 porosimeter; they were calculated by the Washburn relationship with the contact angle theta equal to 140° and the surface tension gamma equal to 485 dynes / cm. Each sample was treated in an oven at 200°C at atmospheric pressure for 2 hours before measurement. The starting weight of the sample placed in a Type 10 penetrometer with an accuracy of 0.001 g was approximately 200 mg.
[0086] The AutoPore® instrument was run using software version IV1.09. No corrections were made to the raw data. The measurement range was 3.59 kPa (0.52 psi) to 413685 kPa (60,000 psi).
[0087] Log Differential Intrusion (mL / g) versus pore size data was analyzed over the pore diameter range of 3.5 nm to 405 μm.
[0088] Particle Size Analysis Particle size analysis of the powders was performed using laser diffraction according to the ISO 13320 standard.
[0089] Determination of roundness ratio (RR) Scanning electron microscopy (SEM) pictures were obtained using a scanning electron microscope Jeol JSM-7610F with the accelerating voltage adjusted to 5 kV. Particles were attached to stubs covered with double-sided graphite tape and then metal-coated with an 8 nm thick layer of iridium. Image analysis was performed using Zen ZEISS software, which includes the "Image Analysis" and "Intellesis" modules.
[0090] For each step of the process, all parameters are explained below.
[0091] The size of the SEM photograph is 1280 × 1024 pixels.
[0092] 1. "Intellesis Learnable Segmentation" This module is used to define particle contours by a machine learning system, which was simultaneously trained on two images from SEM photographs of spherical and non-spherical particles, respectively.
[0093] Parameters: Segmentation = Basic Function 33 - Post-Processing = None
[0094] 2. "Image Analysis" - Setup This step allows further setup to refine the segmentation model, fit it to the target image, and specify the type of result.
[0095] Parameters: Class=2 - Rectangular Frame: Left=0; Top=0; Width=1280; Height=950; Angle=0 - Automatic Segmentation: Min Area=1; Min Hole Area=1; Hole Filling=Yes; Binary=No; Separation=Watershed; Count=7; Min Confidence=0 - Region Filter: Boundary Bottom(Max=949); Boundary Left(Min=0); Boundary Right(Max=1279); Boundary Top(Min=0) - Features: Ratio Feret
[0096] 3. "Image Analysis" - Analysis In this final step, all previous parameters have been applied to the image of interest, and the data is displayed in the software and saved in .csv format.
[0097] raw materials Polymer A: VDF / HFP copolymer (85 / 15 wt / wt) was prepared as described in US Patent Application Publication No. 2003 / 0176608 A1. PVA-1: High molecular weight hydrolyzed poly(vinyl alcohol), degree of hydrolysis 80% - commercially available under the name Alcotex® 80 (Synthomer). PVA-2: High molecular weight hydrolyzed poly(vinyl alcohol), degree of hydrolysis 72.5% - sold under the name Alcotex® 72.5 (Synthomer). PVA-3: High molecular weight hydrolyzed poly(vinyl alcohol), degree of hydrolysis 55% - sold under the name Alcotex® 552P (Synthomer). DA1: Hydroxypropyl methylcellulose ether, having a kinematic viscosity of 80-120 mPa·s at 20° C. in an aqueous solution at a concentration of 2% by weight, commercially available from Dow Chemical under the name Methocel® K100GR. DCE: diethyl carbonate from Sigma Aldrich.
[0098] Example 1 In a 4 L reactor, 2046 g of demineralized water and 1 g of PVA-1 per kg of total VDF monomer were sequentially introduced. The mixture was stirred with a six-bladed rotary impeller operating at a speed of 1300 rpm.
[0099] The oxygen present in the reactor was removed by a sequence of vacuum and nitrogen at a fixed temperature of 20° C. This sequence was repeated three times.
[0100] Then, 71.07 g of DCE and 2.27 g of a solution (75%) of t-amyl perpivalate (from United Initiators) in isododecane were introduced into the reactor.
[0101] 1282 g of VDF was added to the mixture (Rwm=1.59). The reactor was then gradually heated until a first set point temperature of 52° C. was reached. At this temperature, the reactor pressure was fixed at 12 MPa.
[0102] The pressure was kept constant at 12 MPa by feeding 640 g VDF. After this feeding, no more monomer was fed and the pressure started to drop to 8 MPa. A total of 1921 g VDF was charged to the reactor. The temperature of the reactor was then gradually increased to 65°C. The pressure was maintained at 90 MPa, then reduced to 5 MPa, and the polymerization was stopped by degassing the suspension until atmospheric pressure was reached. The polymer was then recovered by filtration and suspended in clean water in a stirred tank. After a washing treatment, the polymer was dried in an oven at 65°C for 12 hours. 1677 g of dry powder was recovered.
[0103] The polymerization times and particle characteristics are shown in Table 1.
[0104] Example 2 In a 4 L reactor, 2180 g of demineralized water and 1.5 g of PVA-1 per kg of total VDF monomer were sequentially introduced. The mixture was stirred with an impeller operating at a speed of 1300 rpm.
[0105] The oxygen present in the reactor was removed by a sequence of vacuum and nitrogen at a fixed temperature of 20° C. This sequence was repeated three times.
[0106] Then, 64.68 g of DCE and 1.55 g of a solution (75%) of t-amyl perpivalate (from United Initiators) in isododecane were introduced into the reactor.
[0107] 1176 g of VDF was added to this mixture (Rwm=1.85). The reactor was then gradually heated until a first set point temperature of 52° C. was reached. At this temperature, the reactor pressure was fixed at 12 MPa.
[0108] The pressure was kept constant at 12 MPa by feeding 794 g of deionized water. After 300 min, the polymerization was stopped by degassing the suspension until atmospheric pressure was reached. The polymer was then recovered by filtration and suspended in clean water in a stirred tank. After a washing process, the polymer was dried in an oven at 65 °C for 12 h. 901 g of dry powder was recovered.
[0109] The polymerization times and particle characteristics are shown in Table 1.
[0110] Example 3 In a 4 L reactor, 3129 g of demineralized water and 1.5 g of PVA-1 per kg of total VDF monomer were sequentially introduced. The mixture was stirred with an impeller operating at a speed of 1300 rpm.
[0111] The oxygen present in the reactor was removed by a sequence of vacuum and nitrogen at a fixed temperature of 20° C. This sequence was repeated three times.
[0112] Then, 23.08 g of DCE and 0.67 g of a solution (75%) of t-amyl perpivalate (from United Initiators) in isododecane were introduced into the reactor.
[0113] 510 g of VDF was added to this mixture (Rwm=6.14). The reactor was then gradually heated until a first set point temperature of 52° C. was reached. At this temperature, the reactor pressure was fixed at 12 MPa.
[0114] The pressure was kept constant at 12 MPa by feeding 351 g of deionized water. After 300 min, the polymerization was stopped by degassing the suspension until atmospheric pressure was reached. The polymer was then recovered by filtration and suspended in clean water in a stirred tank. After washing treatment, the polymer was dried in an oven at 65 °C for 12 h. 386 g of dry powder was recovered. The polymerization time and particle characteristics are detailed in Table 1.
[0115] Example 4 The same procedure as in Example 3 was followed, but 1.5 g of PVA-2 was used per kg of total VDF monomer (Rwm=6.14). 370 g of dry powder was recovered. Polymerization time and particle characteristics are detailed in Table 1.
[0116] Example 5 (Comparative) The same procedure as in Example 1 was followed, but PVA-1 was replaced with 0.4 g DA1 per kg total VDF monomer (Rwm=1.59). 1706 g dry VDF polymer was recovered. Polymerization time and particle characteristics are reported in Table 1.
[0117] Example 6 (Comparative) The same procedure as in Example 1 was followed, but with a stirring speed of 880 rpm (Rwm=1.59). 1678 g of dry VDF polymer powder was recovered. Polymerization time and particle characteristics are detailed in Table 1.
[0118] Example 7 In a 4 L reactor, 3119 g of demineralized water and 0.76 g of PVA-1 per kg of total VDF monomer were successively introduced. The mixture was stirred with an impeller operating at a speed of 1300 rpm.
[0119] The oxygen present in the reactor was removed by a vacuum / nitrogen sequence at a fixed temperature of 20° C. This sequence was repeated three times.
[0120] Next, 0.22 g of acrylic acid and 1.92 g of a solution (75%) of t-amyl perpivalate (from United Initiators) in isododecane were introduced into the reactor. Immediately after, 504 g of VDF were introduced into this mixture (Rwm=6.17). The reactor was then gradually heated until a set point temperature of 55° C. was reached, which corresponded to a pressure of 12 MPa.
[0121] The pressure was kept constant at 12 MPa throughout the polymerization run by feeding an aqueous solution containing 13.54 g of acrylic acid per liter of solution. After 386 minutes, the polymerization was stopped by degassing the suspension until atmospheric pressure was reached. A total of 331 g of acrylic acid solution was charged to the reactor.
[0122] The polymer was then collected by filtration and suspended in clean water in a stirred tank. After washing, the polymer was dried in an oven at 65° C. for 12 hours. 395 g of dry powder was collected. The polymerization time and particle characteristics are detailed in Table 1.
[0123] The SEM photograph of the polymer particles is shown in Figure 1. The amount of particles with RR greater than 0.80 is 84%.
[0124] FIG. 2 shows comparative Polymer A, in which the particle size and shape are outside the scope of the present invention, with a percentage of particles having an RR value greater than 0.80 of 45%.
[0125] Example 8 (Comparative) The same procedure as in Example 2 was followed, but 0.4 g DA1 was used per kg total VDF monomer (Rwm=1.85) and the stirring speed was set at 880 rpm. 833 g dry VDF polymer powder was recovered. Polymerization time and particle characteristics are detailed in Table 1.
[0126] Example 9: The same procedure as in Example 3 was followed, but using 0.5 g PVA-1 / kg total VDF monomer and 1.0 g PVA-3 / kg total VDF monomer. Rwm was 6.18. 375 g dry powder was recovered. Polymerization time and particle characteristics are in Table 1.
[0127] [Table 1]
[0128] Example 10: Stability of VDF polymer powder suspensions 20 g of the VDF polymer powder (d50=28 microns) prepared in Example 4 was poured into a transparent flask in ambient air at room temperature. Then, 100 g of an aqueous solution of DA1 (concentration 1 wt%) was added to the flask and the mixture was vigorously stirred. Stirring was stopped after the powder was dispersed in the aqueous solution and the stability of the suspension was checked every 5 minutes. After 30 minutes, no settling of the VDF polymer particles was observed.
[0129] The experiment was carried out using 20 g of VDF polymer powder (d50=90 microns) prepared in Comparative Example 8. The suspension proved to be unstable and two phases were clearly observed 5 minutes after stirring was stopped.
Claims
1. A VDF polymer powder comprising primary particles having a median particle size d50 of 15-50 microns, measured by laser diffraction according to ISO 13320, and a total pore volume of 0.70-2.00 mL / g, wherein the primary particle is defined as the smallest separate identifiable entity observable by laser diffraction techniques performed according to ISO 13320, and the pore volume is determined by mercury porosimetry according to the test described in the description of the specification.
2. 2. The VDF polymer powder according to claim 1, wherein said primary particles have a rounded shape.
3. 2. The VDF polymer powder according to claim 1, wherein at least 55% by number of the primary particles have a circularity ratio greater than 0.8, said circularity ratio being defined as the ratio between the smallest Feret diameter and the largest Feret diameter, said Feret diameter being defined as the distance between two parallel tangents on opposite sides of the silhouette of the particle, determined by image analysis according to the method described in the specification.
4. 2. The VDF polymer powder of claim 1, wherein said VDF polymer comprises repeat units derived from VDF and, optionally, repeat units derived from the polymerization of one or more ethylenically unsaturated monomers other than VDF.
5. 5. The VDF polymer powder according to claim 4, wherein said ethylenically unsaturated monomer different from VDF is selected from the group consisting of fluorinated monomers, non-fluorinated monomers, and mixtures thereof.
6. The fluorinated ethylenically unsaturated monomer is (i) C2-C8 fluoroolefins; (ii) Formula CH 2 =CH-Rf 0 (wherein Rf0 is a C2-C6 perfluoroalkyl group); (iii) chloro- and / or bromo- and / or iodo-C2 to C6 fluoroolefins; (iv) Formula CF 2 = CFORf 1 (wherein, Rf 1 is a C1-C6 perfluoroalkyl group; (v) Formula CF 2 =CFOX 0 (In the formula, X 0 is a C1-C12 oxyalkyl group or a C1-C12 (per)fluorooxyalkyl group having one or more ether groups; (vi) Formula CF 2 = CFOCF 2 ORf 2 (wherein, Rf 2 is a C1-C6 (per)fluoroalkyl group, or a C1-C6 (per)fluorooxyalkyl group having one or more ether groups; (vii) Formula CF 2 = CFOY 0 (In the formula, Y 0 is selected from C1-C12 alkyl or (per)fluoroalkyl groups, C1-C12 oxyalkyl groups and C1-C12 (per)fluorooxyalkyl groups having one or more ether groups; Y 0 contains a carboxylic or sulfonic acid group in its acid, acid halide or salt form); (viii) fluorodioxole; (ix) vinyl fluoride, and mixtures thereof 6. The VDF polymer powder according to claim 5, selected from the group consisting of:
7. The ethylenically unsaturated non-fluorinated monomer has formula (I): 【Chemistry 1】 (In the formula, - R 1 , R 2 and R 3 are equal to or different from each other and independently represent a hydrogen atom and C 1 ~C 3 is selected from a hydrocarbon group; - R X C includes at least one functional group selected from hydroxyl, carboxyl, epoxide, ester and ether groups. 1 ~C 20 (It is a hydrocarbon part.) 6. The VDF polymer powder according to claim 5, wherein the hydrophilic monomers are selected from the group consisting of:
8. 2. A method for the preparation of a VDF polymer powder according to claim 1, comprising the step of polymerizing VDF and, optionally, one or more ethylenically unsaturated monomers copolymerizable therewith in aqueous suspension in the presence of a water-soluble suspending agent selected from the group of partially hydrolyzed poly(vinyl alcohol) polymers, said polymerization being carried out at an agitation speed N for a given reactor diameter D of: |D| 2/3 ×|N|≧250 in a reactor under stirring, wherein |D| represents the absolute value of the reactor diameter D in meters and |N| represents the absolute value of the stirring speed in rpm.
9. 250≦(|D| 2/3 ×|N|)≦600 The method according to claim 8, wherein
10. 2. A method for the preparation of a VDF polymer powder according to claim 1, comprising the step of polymerizing VDF and, optionally, one or more ethylenically unsaturated monomers copolymerizable therewith in aqueous suspension in the presence of a water-soluble suspending agent selected from the group of partially hydrolyzed poly(vinyl alcohol) polymers, said polymerization being characterized by a Reynolds number Re=ρ.N.d I 2 / μ (where ρ is the density of water (kg / m 3 ), N is the impeller revolutions per second (1 / s), and d I is the impeller diameter (m) and μ is the kinematic viscosity of water at the temperature of the reaction (Pa·s) is greater than 24000, preferably greater than 25000, more preferably greater than 27000, even more preferably greater than 30000.
11. 9. The method of claim 8, wherein the partially hydrolyzed poly(vinyl alcohol) polymer has a degree of hydrolysis of at least 50%.
12. A composition comprising water and the VDF polymer powder of claim 1.
13. The composition according to claim 12, comprising from 20% to 60% by weight of said VDF polymer powder relative to the total weight of said composition.
14. 13. Use of the VDF polymer powder according to claim 1 or the composition according to claim 12 for the production of binders and electrodes for primary and secondary batteries.
15. Use of the VDF polymer powder according to claim 1 or the composition according to claim 12 for producing an article, preferably a membrane or a fibre-reinforced composite material.